The effectiveness of the Finnish pre-seed and seed policy schemes to promote innovative high-growth entrepreneurial ventures - Terttu Luukkonen (The Research Institute of the Finnish Economy (ETLA), 2010)
This report assesses the effectiveness of the supply and demand side policy initiatives in Finland targeted at pre-seed and seed stage businesses, particularly from the viewpoint of high-growth ventures. In order to obtain a yardstick by which to judge the current policy mix in Finland, this study focuses on systemic functions which these policies can be expected to fulfil to promote a viable high-growth entrepreneurial eco-system. When considering the features of major policy initiatives the study draws on analysis of venture capital policies and especially of typical failures in policy initiatives, as presented by Lerner (2009). The study assesses existing pre-seed and seed stage policy schemes and even though the present policy mix has successful elements, it also exhibits serious flaws in programme design and implementation, which may be counteractive to the achievement of the policy objectives. There is also a need to improve overall policy coordination and strategic leadership in the promotion of high-growth ventures.
Keywords: G24; O38; 330; venture capital-directed policy; seed stage initiatives; policy design